2018
DOI: 10.1080/15569527.2018.1495230
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress and antioxidant therapy in acute and chronic phases of sulfur mustard injuries: a review

Abstract: Sulfur mustard (SM) is a chemical compound that preferentially targets ocular, cutaneous and pulmonary tissues. Although pathologic effect of SM has been extensively considered, molecular and cellular mechanism of its toxicity, especially at the chronic phase of injury is not well-understood. Excessive production of reactive oxygen species (ROS) and oxidative stress (OS) appears to be involved in SM-induced injuries. SM may trigger several molecular and cellular pathways linked to OS and inflammation that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 100 publications
0
18
0
Order By: Relevance
“…The fact that the Chemical Weapons Convention has not yet achieved universality and the suspicion that some nations have CWA capabilities (33), urges to find novel treatments for post-exposure disorders. In response to this challenge, ROS scavenging, oxidative/nitrosative stress mitigation, antiinflammatory capability, preservation of membrane and intracellular macromolecules, and abrogation of mitochondrial anoikis equip melatonin for counteracting the cytotoxicity of alkylating agents leading to a promising therapy option (34)(35)(36)(37)(38). Accordingly, melatonin has demonstrated biochemical and morphological protection against the respiratory tract, the bladder and the kidney damage induced by mustard vesicant agents (36,(39)(40)(41)(42)(43).…”
Section: Immune-inflammation and Oxidative Stress Induced By Vesicantmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that the Chemical Weapons Convention has not yet achieved universality and the suspicion that some nations have CWA capabilities (33), urges to find novel treatments for post-exposure disorders. In response to this challenge, ROS scavenging, oxidative/nitrosative stress mitigation, antiinflammatory capability, preservation of membrane and intracellular macromolecules, and abrogation of mitochondrial anoikis equip melatonin for counteracting the cytotoxicity of alkylating agents leading to a promising therapy option (34)(35)(36)(37)(38). Accordingly, melatonin has demonstrated biochemical and morphological protection against the respiratory tract, the bladder and the kidney damage induced by mustard vesicant agents (36,(39)(40)(41)(42)(43).…”
Section: Immune-inflammation and Oxidative Stress Induced By Vesicantmentioning
confidence: 99%
“…In this context, the capacity of melatonin to modulate the inflammation-immune axis (48,49) should mitigate the pathological features induced by sulfur mustard through the modulation of the inflammation-immune axis. Some studies have suggested that the enhancement of oxidative species production or weakening of antioxidant mechanisms are crucial in the acute toxicity of sulfur mustard and long-term effects following acute poisoning (22,38,(50)(51)(52)(53). The powerful nitrosating agent peroxynitrite (ONOO • ) is involved in detrimental effects of all mustards as it covalently modifies all the principal types of biomolecules including membrane lipids, thiols, proteins and purine and pyrimidine bases (54)(55)(56).…”
Section: Immune-inflammation and Oxidative Stress Induced By Vesicantmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24,85 It also leads to the generation of reactive oxygen species, causing oxidative damage to cells and mitochondria as well as the depletion of antioxidant enzymes, such as glutathione. 21,[86][87][88][89][90] Here, we will discuss in detail the changes in miR-NAs in the different biological systems upon SM exposure (Table 1).…”
Section: Role Of Mirnas In Sm-induced Toxicity In Different Physiological Systemsmentioning
confidence: 99%
“…Sulphur mustard is a highly reactive bifunctional alkylating agent, and as such is able to react rapidly with a broad range of cellular constituents and molecular targets. This has resulted in numerous hypotheses being proposed and it has been well recognized as causing the production of reactive nitrogen and oxygen species [ [31] , [32] , [33] , [34] , [35] ], as well as disturbing an array of molecular pathways including; intracellular calcium, anion and pH regulation, poly(ADP-ribose polymerase (PARP) activation, DNA damage and repair, apoptosis induction, inflammation, membrane bound receptors, signalling molecules and extracellular matrices [ 2 , 3 , 11 , 14 , 15 , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. However, the pathways that ultimately lead to toxicity remain elusive and investigators continue their efforts to define the progression of biochemical/molecular events from exposure to the ultimate expression of overt toxicity.…”
Section: Introductionmentioning
confidence: 99%